“Pottery Kilns, Specialized Production, Industrial Area and Chiefdoms”: A Reverse Interpretation of the Archaeological Findings from Tappeh Pardis - Sajjad Alibaigi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
During the excavation at Tappeh Pardis in Varamin, North of the central plateau, several heating structures have been discovered, which were called pottery kiln. Considering the accumulation of this type of structure in the eastern part of the site, they have assumed that these structures are specialized ceramic production in the intensive industrial area of the fifth millennium BC. Therefore, these structures were called the first kilns of this period on the central plateau of Iran. In this article, I try to show, based on several archaeological evidence, that this notion is not correct, and all the interpretations presented on the basis of this evidence should be reviewed. The heating structures from Tappeh Pardis are not unique in the prehistory of Iran, and their samples have been obtained in excavations of several sites, which are also within the settlement area and clearly show the type of ovens. In fact, when the discovered structures are not kilns, the tangible archaeological evidence to belong them as workshops is low, and it would not be possible to accept that large-scale specialized activities, especially in relation to production and bake pottery, have been done in this part. These structures are located among the architectural spaces and various materials like pottery, beads, oyster, Sling, Token, Clay Spindle, bones, etc. have been discovered in there. In fact, the excavator cannot describe the type and function of the kiln and cannot explain the presence of Tokens, Slings and Clay Spindle, baked pottery, animal bone, and carbonized Cereals in excavated deposits? Moreover, how can there be baked pottery and Slag, as well as Slings, flakes, and unbaked tokens? This evidence is enough to doubt the function of structures as a kiln. The documents show that the structures do not have function as kiln, According to them, it is impossible to establish a direct relationship between the nature of the Tappeh Pardis and changes in the social levels of the community. Therefore, it cannot be accepted that these structures are related to the form and structure of society and systems that Fazelin-Neshi and his colleagues called them classified society, elites, and chiefdoms.